Welcoming the Economic Transformation of the Ummah in Aceh through Muslim Friendly Tourism Destinations - Maulana, Nora; Ghafur Wibowo, Muhammad; Ashabul Zicky, Muhammad; Ernita (Syarah: Jurnal Hukum Islam dan Ekonomi, 2024)
This research highlights how tourism management based on religious values or known as Muslim-friendly tourism can invite global tourists, while maintaining a balance between modernity and local wisdom but able to contribute in reducing social inequality, especially poverty fluctuations. This research not only explores the landscape of Aceh as a Muslim-friendly tourist destination, but also identifies alternative strategies in creating a halal tourism ecosystem that supports the image of inclusive economic transformation of the people in Aceh. This research includes descriptive qualitative field research, using the Systematic Literature Review Analytical approach. The data sources used to achieve the research objectives refer to the utilization of primary and secondary data sources. Primary data was obtained through observation, while secondary data was obtained through documentation techniques from various valid relevant sources. The data analysis procedure starts from data reduction, followed by data presentation, conclusion drawing and data verification. The research findings show that Muslim-friendly tourism offers significant opportunities to reduce poverty through the creation of new jobs, empowering MSMEs, encouraging better infrastructure development, increasing sources of diversification of community income, and elevating Aceh's image as a global Muslim-friendly tourist destination. Therefore, the tourism sector can be a locomotive that brings significant changes to the economic landscape of Aceh. With strong collaboration between the government, the community, and the private sector, Aceh has the potential to become one of the leading tourist destinations that is not only economically beneficial, but can also provide spiritual benefits for Muslims around the world. Transforming the ummah's economy through the Muslim-friendly tourism sector is not only about creating economic opportunities, but also about building a better future for future generations. It is a step that, with proper planning and implementation, can lead Aceh to a more prosperous, sustainable, and dignified economy in the eyes of the world.